2020
DOI: 10.1093/cercor/bhaa337
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methyltransferase 3A Is Involved in the Sustained Effects of Chronic Stress on Synaptic Functions and Behaviors

Abstract: Emerging evidence suggests that epigenetic mechanisms regulate aberrant gene transcription in stress-associated mental disorders. However, it remains to be elucidated about the role of DNA methylation and its catalyzing enzymes, DNA methyltransferases (DNMTs), in this process. Here, we found that male rats exposed to chronic (2-week) unpredictable stress exhibited a substantial reduction of Dnmt3a after stress cessation in the prefrontal cortex (PFC), a key target region of stress. Treatment of unstressed cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…The genome-wide molecular changes in response to chronic stress have been extensively characterized (1)(2)(3)(4)(5)(6)(7)(8), as chronic stress is a major risk factor for neuropsychiatric disorders (9)(10)(11)(12). Much less is known about the genome-wide response to acute stress, although the border between acute and chronic stress is diffuse.…”
Section: Molecular Correlates Of Allostasismentioning
confidence: 99%
“…The genome-wide molecular changes in response to chronic stress have been extensively characterized (1)(2)(3)(4)(5)(6)(7)(8), as chronic stress is a major risk factor for neuropsychiatric disorders (9)(10)(11)(12). Much less is known about the genome-wide response to acute stress, although the border between acute and chronic stress is diffuse.…”
Section: Molecular Correlates Of Allostasismentioning
confidence: 99%
“…Given the profound role of the brain as the central organ for stress sensing and response as well as the regulation of systemic stress, the goal of this study was to define the major molecular changes of stress-associated genes and metabolites in an unbiased manner. Previous rodent studies have been predominantly conducted under repeated or chronic stress conditions [ 27 , 28 , 32 , 36 , 39 , 42 , 43 , 47 ]. However, compared to our understanding of the effects of chronic stress, the impacts of acute stress (AS) on the brain remain largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored stress-mediated molecular alterations in the brain [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Some studies have demonstrated transcriptional changes at different time points after stress challenge [ 25 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, overexpression of Dnmt3a in PFC of stressed animals prevented the loss of glutamatergic responses. Chronic stress-induced behavioral abnormalities could be partially attenuated by Dnmt3a expression in PFC ( 65 ). Third, this study only used male rats.…”
Section: Discussionmentioning
confidence: 99%